Assessment of Some Trace Heavy Metals and Radioactivity Concentration in Drinking Water of Saudi Arabia (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Concentration of trace elements and natural gross radioactivity were measured in the drinking water in Jizan region (Saudi Arabia). A preliminary study on trace elements (Zn, Fe, Mn, Ni, Cu, Cr, Co, Se, Sr, V, Ti, Mo, Hg, Cd, Ba, As, Al and Pb) concentrations and natural radioactivity related to gross-α and gross-β radiations in the drinking water were determined. The obtained results showed that, in general, the trace elements concentrations in water did not exceed WHO [1], and GSO [2] guidelines. Generally, heavy metals concentration of the drinking water were found to be in the sequence of Sr > Ti > Fe > Al > Zn > Ba > As > Cu > Mo > Ni > Cr > Co > Se >Hg > Mn, respectively. The results of this study indicated that a general absence of serious pollution in the drinking water used in this region. The results obtained from the radioactivity determination indicate that the drinking water radioactivity concentration of gross-α and gross-β were ranging from 0.06±0.001 to 0.45±0.03 Bq/l and from 0.05±0.006 to 2.95±0.23 Bq/l, respectively. The gross alpha values were found to fall below the GSO and WHO recommended MCL of 0.5 Bq/l while the gross beta values in two samples only exceeds the MCL value of 1 Bq/l, respectively.